If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(5c + -1) + -5 = 20c + 5 Reorder the terms: 5(-1 + 5c) + -5 = 20c + 5 (-1 * 5 + 5c * 5) + -5 = 20c + 5 (-5 + 25c) + -5 = 20c + 5 Reorder the terms: -5 + -5 + 25c = 20c + 5 Combine like terms: -5 + -5 = -10 -10 + 25c = 20c + 5 Reorder the terms: -10 + 25c = 5 + 20c Solving -10 + 25c = 5 + 20c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-20c' to each side of the equation. -10 + 25c + -20c = 5 + 20c + -20c Combine like terms: 25c + -20c = 5c -10 + 5c = 5 + 20c + -20c Combine like terms: 20c + -20c = 0 -10 + 5c = 5 + 0 -10 + 5c = 5 Add '10' to each side of the equation. -10 + 10 + 5c = 5 + 10 Combine like terms: -10 + 10 = 0 0 + 5c = 5 + 10 5c = 5 + 10 Combine like terms: 5 + 10 = 15 5c = 15 Divide each side by '5'. c = 3 Simplifying c = 3
| -x-4=18 | | 5x^2+5x-360=0 | | 45=21+(5-1)d | | 4c=6+3c | | 7x^2-49x-210=0 | | 30+2y-9=9y-14-2y | | 3/2.5=(x+3)/9.5 | | 79-3x=25 | | 6x^2-72x+192=0 | | C=mx+3 | | 6x^2+24x-462=0 | | (-p^4/-5p^3)^-2 | | -7=9-2x+2 | | (6-9)(3-6)= | | 1=x-4+5 | | 525+0.21x=850.00 | | 5+(12-1)1/3= | | X+23+4x=-39-4x-46 | | -9+10= | | 3(y+2)=14 | | (2-9)(4-2)= | | 3(2h+1)-2(h+3)=2(h-3)-1 | | 2x+25=12x-122 | | 2x+25=14x-122 | | 1/x=9/4x+5 | | X^3-27y^3=0 | | x^3+2x^2+5x=-10 | | 23 + 4 (y) - 2 + 18 = 59 | | 3/2y=9 | | 23 + 4 x y - 2 + 18 = 59 | | 6(x-1)-3=3(x-4) | | X^4+x^3-20x^2=0 |